ӨЗБЕК, ТҮРКМЕН, ҚАРАҚАЛПАҚ ПОЭЗИЯСЫНДА КӨРКЕМ ФОРМАЛЫҚ ИЗЛЕНИСЛЕР - Гайлиева, О.К. (SCIENCE and SOCIETY, 2018)
In the article there are considered the artistic searches of the poets and their skill in creation of new artistic forms in the Uzbek, Turkmen can Karakalpak poetry of the XX-th century.
Keywords: traditional forms; new forms; poetics; a gazelle; an ahruz; artistic searches; skill